Microenvironmental G protein‐coupled estrogen receptor‐mediated glutamine metabolic coupling between cancer‐associated fibroblasts and triple‐negative breast cancer cells governs tumour progression - Chongwu He; Meixi Peng; Xiaoqiang Zeng; Hanzhi Dong; Zhengkui Sun; Jiawei Xu; Manran Liu; Liyan Liu; Yanxiao Huang; Zhiqiang Peng; Yu‐An Qiu; Chunling Jiang; et al. (Clinical and Translational Medicine)
Abstract Background Triple‐negative breast cancer (TNBC) is a particularly aggressive type of breast cancer, known for its lack of effective treatments and unfavorable prognosis. The G protein‐coupled estrogen receptor (GPER), a novel estrogen receptor, is linked to increased malignancy in various cancers. However, its involvement in the metabolic regulation of cancer‐associated fibroblasts (CAFs), a key component in the tumour microenvironment, remains largely unexplored. This study investigates how GPER influences the metabolic interaction between CAFs and TNBC cells, aiming to identify potential therapeutic targets. Methods The co‐culture system is performed to examine the interaction between CAFs and TNBC cells, with a focus on GPER‐mediated glutamine production and release by CAFs and its subsequent uptake and utilization by TNBC cells. The definite roles of microenvironmental GPER/cAMP/PKA/CREB signalling in regulating the expression of glutamine synthetase (GLUL) and lactate dehydrogenase B (LDHB) are further investigated. Results Our findings reveal that estrogen‐activated GPER in CAFs significantly upregulates the expression of GLUL and LDHB, leading to increased glutamine production. This glutamine is then secreted into the extracellular matrix and absorbed by TNBC cells, enhancing their viability, motility, and chemoresistance both in vitro and in vivo. TNBC cells further metabolize the glutamine through the glutamine transporter (ASCT2) and glutaminase (GLS1) axes, which, in turn, promote mitochondrial activity and tumour progression. Conclusions The study identifies GPER as a critical mediator of metabolic coupling between CAFs and TNBC cells, primarily through glutamine metabolism. Targeting the estrogen/GPER/glutamine signalling axis in CAFs offers a promising therapeutic strategy to inhibit TNBC progression and improve patient outcomes. This novel insight into the tumour microenvironment highlights the potential of metabolic interventions in treating TNBC. Key points Estrogen‐activated GPER in CAFs enhances GLUL and LDHB expression via the cAMP/PKA/CREB signalling, facilitating glutamine production and utilization. Microenvironmental GPER‐induced glutamine serves as a crucial mediator of metabolic coupling between CAFs and TNBC cells, boosting tumour progression by enhancing mitochondrial function. Targeting the glutamine metabolic coupling triggered by estrogen/GPER/GLUL signalling in CAFs is a promising therapeutic strategy for TNBC treatment.